A head-to-head comparison among donor site morbidity after vascularized lymph node transfer: Pearls and pitfalls of a 6-year single center experience - SAÇAK, BÜLENT (My University, 2017)
Between 2010 and 2016, 110 patients with extremity lymphedema underwent vascularized lymph node (VLN) transfer: groin (G-VLN = 20), supraclavicular (SC-VLN = 54), and right gastroepiploic (RGE-VLN = 36) open and laparoscopic approach. Herein, we discuss the pearls and pitfalls for VLN harvest and compare donor site morbidity and complications. Lymphatic leakage: G-VLN (n = 1) and SC-VLN (n = 1) and one hematoma: SC-VLN were found. Laparoscopic harvest of the RGE-VLN reduces donor site morbidity. However, surgeons experience is imperative to minimize donor site morbidity and complications. (C) 2016 Wiley Periodicals, Inc.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; Surgery Medicine Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); CERRAHİ; ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); SURGERY; Cerrahi; Surgery; lymphedema; donor site morbidity; lymph node flap transfer; vascularized lymph node transfer; lymphaticovenous anastomosis; FLAP TRANSFER; TRANSPLANTATION; COMPLICATIONS; ANASTOMOSIS; REGION